Clutter Effect on a Combination of Microwave Imaging and Target Identification Using Ground-Penetrating Radar - Kiattisak Yochanang; Lakkhana Bannawat; Akkarat Boonpoonga; Chuwong Phongcharoenpanich (IETE Journal of Research, 2023)
AbstractThis paper presents an experimental investigation of the effect of clutter on the performance of microwave imaging and target identification using ground-penetrating radar (GPR) for buried objects. Signals collected by the GPR were formed to be B-scan and 3D images to carry out the microwave imaging of buried objects. Poles extracted using the short-time matrix pencil method from a late-time response of the received signal collected at a specific position were exploited to identify buried objects. The experiment was set up by constructing a large box filled with sand where an L-shaped metallic sheet was buried. The GPR was installed along with a 2-dimensional scanner above the box to image and identify the buried metallic sheet. In order to investigate the effect of the clutter on the performance of the GPR-based microwave imaging and target identification, small rocks were arranged on the sand surface, and their density was then varied. The experimental results have shown that clutter density significantly affects the sharpness of the B-scan and 3D images. The rocks result in an additional surface layer in the images. Moreover, the results have also shown that the clutter does not affect the performance of the identification of the buried object. From the results, the poles obtained from the GPR scanning inside and outside the buried object region differed. This confirms that the poles of the buried object should be different from those without the object. The poles of the buried object remain constant, although rocks on the sand surface exist since the clutter affects only the early-time response (not the late-time response). With varying clutter densities, the underlying poles were significantly changed, but this does not affect the identification of the buried object.KEYWORDS: Clutter effectGround-penetrating radarGPRMicrowave imagingTarget identificationShort-time matrix pencil methodSTMPM AcknowledgmentsThis research was funded in part by the National Science, Research and Innovation Fund (NSRF), and King Mongkut's University of Technology North Bangkok, Contract no. KMUTNB-FF-65-26, and in part by the Office of the Permanent Secretary, Ministry of Higher Education, Science, Research and Innovation under grant number RGNS 63-102. Also, the Department of Computer Engineering, Faculty of Engineering, Rajamangala University of Technology Rattanakosin is gratefully acknowledged.Disclosure statementNo potential conflict of interest was reported by the author(s).Additional informationFundingThis work was supported by Office of the Permanent Secretary, Ministry of Higher Education, Science, Research and Innovation: [grant number RGNS 63-102]; National Science, Research and Innovation Fund (NSRF) and King Mongkut's University of Technology NorthBangkok: [grant number KMUTNB-FF-65-26].Notes on contributorsKiattisak YochanangKiattisak Yochanang was born in Samut-Songkhram, Thailand, in 1980. He received the BS.tech.ed. (1st Class hons.) degree in computer technology and the MEng. degree in electrical engineering from the King Mongkut's University of Technology North Bangkok (KMUTNB), Thailand, in 2003, 2007, respectively. He is currently pursuing the PhD. degree in electrical engineering. His research interest includes microwave imaging and ground-penetrating radar (GPR). Email: kiattisaky@kmutnb.ac.thLakkhana BannawatLakkhana Bannawat received the B.Eng. degree in computer engineering from Mahanakorn University of Technology (MUT), Bangkok, Thailand, in 2011, and the MEng. degree in electrical engineering and the PhD. degree in electrical engineering from King Mongkut's Institute of Technology North Bangkok (KMUTNB), Bangkok, in 2014 and 2019, respectively. She is currently an Assistant Professor with the Department of Computer Engineering, Faculty of Engineering, Rajamangala University of Technology Rattanakosin (RMUTR), Nakhon Pathom, Thailand. Hers research interests include ground-penetrating radar (GPR), radar systems, radar target identification, RFID, IoT, and signal processing for EM applications. Corresponding author. Email: lakkhana.ban@rmutr.ac.thAkkarat BoonpoongaAkkarat Boonpoonga received the BEng. degree in electrical engineering from King Mongkut's University of Technology North Bangkok (KMUTNB), Bangk-ok, Thailand, in 2002, and the M.Eng. degree in telecommunications engineering and the D.Eng. degree in electrical engineering from King Mongkut's Institute of Technology Ladkrabang (KMITL), Bangkok, in 2004 and 2008, respectively. He is currently an Associate Professor with the Department of Electrical and Computer Engineering, Faculty of Engineering, KMUTNB. His research interests include ground-penetrating radar (GPR), radar systems, radar target identification, the chipless RFID systems, and signal processing for EM applications. He is a member of ECTI Association. He was a Board Committee Member of ECTI Association, Thailand, from 2016 to 2017 and 2020 to 2021. Email: akkarat.b@eng.kmutnb.ac.thChuwong PhongcharoenpanichChuwong Phongcharoenpanich received the BEng. (Hons.), MEng., and DEng. degrees from the King Mongkut's Institute of Technology Ladkrabang (KMITL), Bangkok, Thailand, in 1996, 1998, and 2001, respectively. He is currently a professor with the Department of Telecommunications Engineering, KMITL, where he also serves as the Leader for the Innovative Antenna and Electromagnetic Applications Research Laboratory. His research interests include antenna design for various mobile and wireless communications, conformal antennas, and array antenna theory. He is a Senior Member of IEICE and a member of ECTI. He has been on Organizing Committee of several international conferences, including the TPC Chair of 2009 International Symposium on Antennas and Propagation (ISAP 2009) and a TPC Member of ISAP 2012. He was on the Board Committee of ECTI Association, from 2008 to 2011 and from 2014 to 2015. He has served as the Chair for the IEEE MTT/AP/ED Thailand Chapter, from 2014 to 2018. He is also a Reviewer of many scientific journals, including the IEEE TRANSACTIONS ON ANTENNAS AND PROPAGATION, IEEE ACCESS, IET Microwaves, Antennas and Propagation Electronics Letters, ECTI Transactions, and many international conferences, including ISAP and APMC. He was an Associate Editor of the IEICE Transactions on Communications and the ECTI Transactions on Electrical Engineering, Electronics, and Communications. He is also an Associate Editor of the IEICE Communications Express. Email: chuwong.ph@kmitl.ac.th
Keywords: Geophysical Methods and Applications; Microwave Imaging and Scattering Analysis; Advanced SAR Imaging Techniques